(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to determine the seroprevalence of anisakiasis and its associated risk factors in the Sangihe Islands Regency, Indonesia, where people have a unique habit of consuming raw seafood “Kinilo.” Materials and Methods: This cross-sectional study involved 112 respondents who met the inclusion criteria using the Indirect ELISA method with the Anisakidae immunoglobulin G (IgG) kit. Results: The results showed that 59/112 respondents (52.67%) were seropositive for Anisakidae IgG, with significant risk factors such as the consumption of Katsuwonus pelamis and measures related to eating habits. Multivariate analysis revealed that consumption of raw K. pelamis was associated with a 45.748 times higher risk of anisakiasis. Conclusion: These findings highlight the need to raise awareness and implement interventions to prevent infection, including fish processing and storage education. This study emphasizes the need for a holistic health approach to reduce the risk factors for anisakiasis in at-risk communities. J. Adv. Vet. Anim. Res., 12(1): 8–18, March 2025 http://doi.org/10.5455/javar.2025.l867